Shaming, Blaming, and Maiming: Functional Links Among the Moral Emotions, Externalization of Blame, and Aggression - Stuewig, Jeffrey (2010)
Theory suggests that shame should be positively related to aggression while guilt may serve as a protective factor. Little research has examined mediators between the moral emotions and aggression. Results using path analyses in four diverse samples were consistent with a model of no direct relationship between shame-proneness and aggression. There was, however, a significant indirect relationship through externalization of blame, but mostly when aggression was measured using self-report. Guilt-proneness, on the other hand, showed a direct negative relationship to aggression whether using self-report or other reports of aggression. Guilt was also inversely related to aggression indirectly through externalization of blame and empathy. Identifying these differing mechanisms may be useful in developing more effective interventions for aggressive individuals.